Stereology of gonadotropin-releasing hormone and kisspeptin neurons in PACAP gene-deficient female mice - Barabás, Klaudia; Kovács, Gergely; Vértes, Viola; Kövesdi, Erzsébet; Faludi, Péter; Udvarácz, Ildikó; Pham, Dániel; Reglődi, Dóra; Abraham, Istvan M.; Nagy, Zsuzsanna (Frontiers in Endocrinology, 2022)
The hypothalamic gonadotropin-releasing hormone (GnRH)-kisspeptin neuronal network regulates fertility in all mammals. Pituitary adenylate cyclase-activating polypeptide (PACAP) is a neuropeptide isolated from the hypothalamus and is involved in the regulation of several releasing and trophormones. It is well-known that PACAP influences fertility at central and peripheral levels. However, the effect of PACAP on GnRH and kisspeptin neurons is not well understood. In our study, we first investigated the integrity of the estrous cycle in PACAP knockout (KO) mice. We determined the number and the fiber density of GnRH neurons of wild type (WT) and PACAP KO female mice using immunohistochemistry. In addition, we measured the number of kisspeptin neurons by counting kisspeptin mRNA positive cells in the rostral periventricular region of the third ventricle (RP3V) and arcuate nucleus (ARC) using RNAscope technique. Finally, estrogen receptor alpha (ERα) mRNA and protein expression were also examined. Our data showed that the number of complete cycles decreased, and length of each cycle was longer in PACAP KO mice. Furthermore, PACAP KO mice experienced longer periods of diestrus and spent significantly less time in estrus. We observed no difference in the fiber density or the number of GnRH neurons. In contrary, the number of kisspeptin neurons was decreased in the ARC but not in the R3PV in PACAP KO mice compared to WT littermates. Furthermore, the ERα mRNA and protein expression was decreased in the ARC whereas in the R3PV region mRNA levels of ERα was elevated. Our results demonstrate that embryonic deletion of PACAP significantly changes the structure and presumably the function of GnRH-kisspeptin neuronal network influencing fertility.